Economic evaluation of maintenance strategies for ground-mounted solar photovoltaic plants. (1st August 2017) - Peters, Lennart; Madlener, Reinhard
Highlights: A generic model for the economic analysis of PV maintenance strategies is proposed. We investigate open-field PV plants of different size and with variable components. We compare immediate corrective maintenance with alternative maintenance strategies. Immediate corrective maintenance is found to be the most cost-effective strategy. Higher costs per service trip and larger PV plants favor periodic maintenance. Abstract: We propose a generic model which allows to evaluate the economic viability of alternative maintenance strategies for differently sized photovoltaic plants with variable components. We thoroughly review the existing literature on reliability, maintenance and maintenance strategies for PV plants. The model is applied to fixed-tilt ground-mounted solar PV plants in Germany of three different sizes: 1, 10, and 100 MWp . The PV plants are set up in a central inverter configuration with the following components: AC/DC switch, circuit breaker, and inverter. The analysis compares immediate corrective maintenance with maintenance strategies of different periodicity (weekly, bi-weekly, and monthly). Simulations take the driving time of the service team and the operation of a spare parts inventory into account. We further analyze the impact of hourly spot prices in contrast to constant prices (feed-in tariffs). We find that corrective maintenance is the most cost-efficient strategy. If the service journey takes six hours instead of one hour, corrective maintenance becomes more expensive than weekly periodic maintenance. For a three-hour journey, the size of the PV plant matters. If corrective maintenance is adopted, the establishing of a spare parts inventory should be considered. When volatile hourly spot prices are considered, we find that opportunity costs are lowest (highest) when service teams operate at 8 pm (8 am), irrespective of the day of the week, whereas maintenance events scheduled for Wednesdays at 8 am or 2 pm are, given current EPEX spot prices, the most cost-efficient in terms of total costs.